1992
DOI: 10.1785/bssa0820041661
|View full text |Cite
|
Sign up to set email alerts
|

Love-wave propagation in a three-dimensional sedimentary basin

Abstract: A simplified three-dimensional finite-element method has been developed for simulation of Love-wave propagation in three-dimensional sedimentary basins. The eigenfunctions for the fundamental-mode surface waves are employed as interpolation functions in the finite-element scheme. By reducing the number of degrees of freedom, the method enables us to analyze wave propagation in an area of 2000 km2 as large as the southern part of the Kanto plain, Japan. Time histories of the near Izu-Ohshima earthquake of 1990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…the analogy between the travel paths from the major asperities (Wald and Somerville, 1995) and from the 1990 Odawara earthquake. However, modeling the later phases following the direct surface waves using the fiat-layered model proves ineffective and requires a two-or three-dimensional crustal model including the sedimentary basin (e.g., Kudo, 1980;Liu and Heaton, 1984;Vidale and Helmberger, 1988;Yamanaka et aL, 1989Yamanaka et aL, , 1992Toshinawa and Ohmachi, 1992;Kato et aL, 1993;Hisada et al, 1993;Graves, 1993). This problem will be addressed in future work.…”
Section: Estimation Of Source Model By Grid-search Technique Using Bo...mentioning
confidence: 99%
“…the analogy between the travel paths from the major asperities (Wald and Somerville, 1995) and from the 1990 Odawara earthquake. However, modeling the later phases following the direct surface waves using the fiat-layered model proves ineffective and requires a two-or three-dimensional crustal model including the sedimentary basin (e.g., Kudo, 1980;Liu and Heaton, 1984;Vidale and Helmberger, 1988;Yamanaka et aL, 1989Yamanaka et aL, , 1992Toshinawa and Ohmachi, 1992;Kato et aL, 1993;Hisada et al, 1993;Graves, 1993). This problem will be addressed in future work.…”
Section: Estimation Of Source Model By Grid-search Technique Using Bo...mentioning
confidence: 99%
“…Horike et al (1990) compared the differences in the amplification effect of ground shaking between 3D and 2D basins and found that the 2D model does not represent the magnitude and duration of the ground shaking in the 3D model. Toshinawa and Ohmachi (1992) used a 3D finite element method to simulate the propagation of Love waves in the Kanto Basin, Japan. They determined that the 3D model yields a larger amplitude and longer duration of ground shaking than the 2D model, and the simulation results obtained by the 3D model were closer to the observed record than those obtained by the 2D model.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, seismologists have introduced various numerical methods to simulate long-period ground motions (finite element method, discrete wave number method, and spectral element method) (Toshinawa et al 1992;Aoi et al 1999;Komatitsch et al 1999;Graves et al 2008;Takemura et al 2015). Graves et al ( 2008 ) simulated the broadband ground motion of three Mw 7.8 rupture scenarios of the southern San Andreas fault.…”
Section: Introductionmentioning
confidence: 99%